IRAK-M Deficiency Promotes the Development of Type 1 Diabetes in NOD Mice - Tan, Qiyuan (American Diabetes Association, 2014)
Type 1 diabetes mellitus (T1DM) is an organ-specific autoimmune disease characterized by progressive destruction of insulin-secreting pancreatic β-cells. Both T-cell–mediated adaptive responses as well as innate immune processes are involved in pathogenesis. Interleukin-1 receptor–associated kinase M (IRAK-M) can effectively inhibit the MyD88 downstream signals in Toll-like receptor pathways, while lack of IRAK-M is known to be associated with autoimmunity. Our study showed that IRAK-M–deficient (IRAK-M(−/−)) nonobese diabetic (NOD) mice displayed early onset and rapid progression of T1DM with impaired glucose tolerance, more severe insulitis, and increased serum anti-insulin autoantibodies. Mechanistic studies showed that the enhanced activation and antigen-presenting function of IRAK-M(−/−) antigen-presenting cells from IRAK-M(−/−) mice were responsible for the rapid progression of disease. Moreover, IRAK-M(−/−) dendritic cells induced enhanced activation of diabetogenic T cells in vitro and the rapid onset of T1DM in vivo in immunodeficient NOD mice when cotransferred with diabetogenic T cells. This study illustrates how the modulation of innate immune pathways through IRAK-M influences the development of autoimmune diabetes.